2014
DOI: 10.2298/jas1403275b
|View full text |Cite
|
Sign up to set email alerts
|

Changes in alfalfa cell wall structure during vegetation

Abstract: The investigation was done on 141 samples of one alfalfa cultivar, collected from the same location during the first three growth cycles: spring growth, the first and the second regrowth. Within each growth cycle, sampling was done during the whole growing period, commencing when plant height was below 150 mm and continuing until plants were bearing ripe seeds. On all collected samples the following cell wall characteristics were determined: neutral detergent fibre (NDF), acid detergent fibre (ADF), acid deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…However lignin was indigestible and reduced fiber digestibility in ruminants (Undersander et al, 2009). ADL contents were determined in previous studies as 7.4 % (Malushi et al, 2017), 4.0-5.0% (Sulc et al, 2017), 6.21% (Boziskovic et al, 2014), 4.62-7.32% (Kertikova et al, 2014), 7.1-7.8% (Yari et al, 2014) and 7.36% (Dale et al, 2012). Our findings indicated that ADL contents of alfalfa genotypes were within reasonable limits.…”
Section: Resultsmentioning
confidence: 99%
“…However lignin was indigestible and reduced fiber digestibility in ruminants (Undersander et al, 2009). ADL contents were determined in previous studies as 7.4 % (Malushi et al, 2017), 4.0-5.0% (Sulc et al, 2017), 6.21% (Boziskovic et al, 2014), 4.62-7.32% (Kertikova et al, 2014), 7.1-7.8% (Yari et al, 2014) and 7.36% (Dale et al, 2012). Our findings indicated that ADL contents of alfalfa genotypes were within reasonable limits.…”
Section: Resultsmentioning
confidence: 99%